Botanical Visualization of Huge Hierarchies - Ernst Kleiberg; Huub van de Wetering; Jarke J. van Wijk (InfoVis'01: Proceedings of the IEEE Symposium on Information Visualization, 2001)
A new method for the visualization of huge hierarchical data structures is presented. The method is based on the observation that we can easily see the branches, leaves, and their arrangement in a botanical tree, despite of the large number of elements. The strand model of Holton is used to convert an abstract tree into a geometric model. Nonleaf nodes are mapped to branches and child nodes to subbranches. A naive application of this model leads to unsatisfactory results, hence it is tailored to suit our purposes better. Continuing branches are emphasized, long branches are contracted, and sets of leaves are shown as fruit. The method is applied to the visualization of directory structures. The elements, directories and files, as well as their relations can easily be extracted, thereby showing that the use of methods from botanical modeling can be effective for information visualization.